(untitled) (AYUSHDHARA, 2020)
Our ancient seers have given importance to Shirah (head) as it is part of the body where life along with sense faculties resides. All the sense organs and the channels carrying the sensory and vital impulses from the Shir (head) are like the rays of the sun. It is necessary to care for Urdhvajatru. In Ayurveda classics mentioned the concept of Pathya (wholesome) and Apathaya (unwholesome) as a part of the treatment of the diseases also a part of regime of healthy living. A person needs to follow a healthy diet and regimen so as to prevent any anomalies in life or to maintain good health. Shalakya Tantra has mentioned proper diet to take in particular disease which is necessary to enhance the effect of treatment and prevent the disease and also useful procedures which are part of Dinacharya to maintain routine health. The aim is to evaluate the role of Pathya- Apathya and dietary regimen mentioned in Shalakya Tantra to prevent the supraclavicular disease. Relevant Ayurveda and modern literature, available information on internet etc, were searched. The dietary advice and various Dinacharya modalities gives nourishment to the supra clavicular region and cures ailments of related and also provides preventive and curative benefits.